Evaluation of Economic Disparities in Lithuanian Regions - Misiūnas, Algimantas; Svetikas, Žymantas (Ekonomika, 2003)
The article validates the relevance of the usage of integral indexes in order to estimate municipalities’ condition of the distinct economical spheres on the grounds of 2001 year data. After Lithuanian accession into EU the possibility to reduce regional economic disparities by redirecting ES structural funds allocations to problematic regions will occur. Thus the proper consideration should be attributed to the identification of those regions.The article concentrates on employment, industry and business effectiveness sectors. The usage of average index (evaluations are made by comparing to state average) and MIN/MAX index (evaluations are made by comparing to municipalities minimum and maximum values) is being justified.When counting integral employment index the following indicators were evaluated: the number of old-age and disablement pensioners per 1000 residents, the number of dead per 1000 residents, the number of employees without insurance, official rate of unemployment, the rate of permanent unemployment. The estimation of the industry index is based on the following indicators: industrial production sold, the extent of construction works, covering of agricultural production; the services provided.The business activities are unequally distributed among Lithuanian regions and the results of the entrepreneurs in the regions are diverse. When counting business index for Lithuanian regions the most important for the enterprises indicators were analyzed: the sales gross profitability, activity profitability coefficient, capital profitability, capital turnover.The article presents ten municipalities in the best condition and ten municipalities in the worst condition according to the above-mentioned employment, industry and business effectiveness sectors.